Construction of Tabuh Gilak Ravana among Sekaa Gong children of Singakerta Village | Pembinaan Tabuh Gilak Rahwana Di Kalangan Sekaa Gong Anak-Anak Desa Singakerta - I Ngurah Edy Upadana (GHURNITA: Jurnal Seni Karawitan, 2024)
Singakerta Village has two sekaa gongs, namely Sekaa Gong Kerta Yowana and Sekaa Gong Children of Singakerta Village. Sekaa Gong Kerta Yowana was formed around late 2014. Sekaa Gong Kerta Yowana was formed around the end of 2014, but its activities stopped around the end of late 2019. To form a new generation called Sekaa Gong Children of Singakerta Village in early 2023. Thematic Real Work Lecture (KKNT) activities exist for students to conduct coaching on Sekaa Gong for Singakerta Village Children with Gilak Ravana Tabuh Material. The method used in fostering tabuh gilak ravana, namely the Training Method, means the determination of the delivery method used during the training, and the author also uses several methods in fostering Sekaa Gong for Singakerta Village Children, such as meguru kuping, meguru panggul, meguru dingdong, and meguru rasa. Tabuh Gilak Ravana was created by Mr. I Wayan Bratha. Tabuh Gilak Ravana depicts the character of Ravana, an antagonist who embodies wrath and human sins. Tabuh Gilak Ravana is implemented using Gong Kebyar gamelan barungan. Tabuh Gilak Ravana uses 32 (thirty-two) beats in one melody, and in its presentation, there are basic punch techniques in playing gamelan, such as the kekenyongan technique. In addition to fostering, they also participate in coral cadet activities, namely helping community service activities such as mutual cooperation, ngayah, etc.